2011
DOI: 10.1007/s00404-011-1839-4
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical markers predicting pre-term delivery in symptomatic patients: phosphorylated insulin-like growth factor binding protein-1 and fetal fibronectin

Abstract: The phIGFBP-1 test may be better that the fFN test in predicting pre-term delivery before 34 weeks' gestation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0
2

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 15 publications
2
19
0
2
Order By: Relevance
“…5 Riboni et al found slightly higher predictive values for phIGFBP-1 test than FFN test in predicting pre-term delivery. 4 They observed that phIGFBP-1 and FFN test had a high specificity and a high negative predictive value in predicting pre-term delivery within 7 days (specificity 83.7 Vs 80.2, NPV 97.7 Vs 97.6) before 34 weeks (specificity 85.7 Vs 82.5, NPV 97.1 Vs 96.4) and before 37 weeks (specificity 89.2 Vs 85.9 NPV 90.8 Vs 88) gestation. Another study by Audibert et al found FFN alone or in combination with cervical length had better predictive accuracy than phIGFBP-1 for delivery within 2 weeks.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…5 Riboni et al found slightly higher predictive values for phIGFBP-1 test than FFN test in predicting pre-term delivery. 4 They observed that phIGFBP-1 and FFN test had a high specificity and a high negative predictive value in predicting pre-term delivery within 7 days (specificity 83.7 Vs 80.2, NPV 97.7 Vs 97.6) before 34 weeks (specificity 85.7 Vs 82.5, NPV 97.1 Vs 96.4) and before 37 weeks (specificity 89.2 Vs 85.9 NPV 90.8 Vs 88) gestation. Another study by Audibert et al found FFN alone or in combination with cervical length had better predictive accuracy than phIGFBP-1 for delivery within 2 weeks.…”
Section: Discussionmentioning
confidence: 99%
“…3 The phIGFBP-1 and FFN bedside dipstick tests hold the promise in identifying those symptomatic women who are least likely to deliver prematurely. 4,5 Studies have been done to predict accuracy of phIGFBP-1 and FFN. 6,7 There have been attempts to combine cervical length with either FFN or phIGFBP-1 to improve the accuracy, however with inconsistent results.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Die breitesten Erfahrungen liegen für das fetale Fibronektion (fFn) vor [17]. In den letzten Jahren wurden Tests auf phosphoryliertes (ph)IGFBP-1 [18] und "placental α-microglobulin-1" (PAMG-1) [19] eingeführt, deren Aussagekra gegenüber dem Fibronektinnachweis höher sein soll. Allen Tests gemeinsam ist die hohe negative Vorhersagekra von über 97%.…”
Section: Biochemische Testsunclassified
“…The tests are designed to detect the presence of specific biochemical markers associated with preterm birth at concentrations higher than those found in background cervicovaginal fluids. A smaller subset of studies has compared directly the performance of these tests to each other, and while the fFN and phIGFBP-1 tests have proven comparable in several studies [17], the PAMG-1 test was found to be significantly more accurate than the fFN test [18].…”
Section: Introductionmentioning
confidence: 99%